Knowledge creation and sharing: Geographical and network perspectives - Schiffauerova, Andrea; Beaudry, Catherine (2010)
This paper brings together our findings on the importance of the geographical proximity and the network structure in the knowledge creation and sharing in Canadian biotechnology and nanotechnology. We find that most of the knowledge sharing occurs inside the geographical clusters or in the proximate distance.However, very distant or overseas collaborations are preferred over the mid-range distance options.We examine the structural properties of the knowledge networks and relate them to their efficiency in knowledge creation and transmission. We conclude that both geographical and network dimensions promote innovation and propose to search for individuals who span the two dimensions.